PEMBENTUKAN CIVIC DISPOSITION PADA PESERTA DIDIK DI MADRASAH ALIYAH NEGERI KOTA SINGKAWANG - Latipa Latipa; Sulistyarini Sulistyarini; Thomy Sastra Atmaja (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aimed to find out how civic disposition students in MAN of Singkawang City was formed. The methodology used in this research was descriptive study in the form of qualitative research. Subjects of this research were the vice principal of students affairs, PPKn teacher, BK teacher, and students. These data subjects were selected based on certain considerations. The techniques data collection were observation, interview, and documentation. The techniques of data analysis consisted data reduction analysis, data presentation, and conclusion. The findings showed that the formation civic disposition in PPKn learning was done through lesson plan which was adapted from character building, implementing the PPKn learning which was integrated with character building and attitude assessment done by PPKn teacher. In addition, the formation civic disposition was also done outside the learning process through routine activities, spontaneity, conditioning, and exemplary. The civic disposition of the students was said to be good. It was marked by the emergence private and public characters. Private characters included self discipline, respecting the worth and dignity every human being from every individual, and being morally responsible. On the other hand, public characters included caring towards others, being polite and courteous, doing deliberation, and able to compromise.